Four new species of the genus Eophileurus Arrow, 1908 (Coleoptera: Scarabaeidae: Dynastinae) from Thailand and Vietnam, with notes on some Indochinese species - Yang, Qiao-Zhi; Pathomwattananurak, Wuttipon (Zootaxa, 2022)
Four new species of the genus Eophileurus Arrow, 1908 are described: E. minor Yang & Pathomwattananurak, new species (Thailand and Vietnam), E. prelli Yang & Pathomwattananurak, new species (Vietnam), E. quadratifovealis Yang & Pathomwattananurak, new species and E. sidereus Yang & Pathomwattananurak, new species (both Thailand). Two new junior synonyms are proposed: E. confinis Prell, 1913 = E. takakuwai Yamaya & Muramoto, 2008, new synonym and E. felschei Prell, 1913 = E. grossepunctatus Dupuis, 2014, new synonym. Lectotypes for E. andamanicus Arrow, 1914 and E. siamensis Arrow, 1914 are designated. Taxonomic problems regarding E. confinis and E. malyi Endrődi, 1978 are discussed. Type material of E. andamanicus, E. confinis, E. decipiens Prell, 1913, E. felschei, E. gracilis Prell, 1913, E. grossepunctatus, E. malyi, E. nicobarensis Endrődi, 1978 and E. siamensis is illustrated. A distribution map of the new species and their closest relatives is also provided.